2006
DOI: 10.1667/rr3528.1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Low-Level Radiation on the Death of Male Germ Cells

Abstract: Hormetic and adaptive responses induced by low-level radiation in hematopoietic and immune systems have been observed, as shown by stimulatory effects on cell growth and resistance to subsequent radiation-induced cytogenetic damage. However, in terms of cell death by apoptosis, the effects of low-level radiation are controversial: Some studies showed decreased apoptosis in response to low-level radiation while others showed increased apoptosis. This controversy may be related to the radiation doses or dose rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 32 publications
1
55
0
1
Order By: Relevance
“…This finding may be one of the reasons for diminished sperm count after exposure of spermatogonia. The increased apoptosis is most likely associated with increased levels of Trp53 protein [43]. As Yin et al [46] note, predominant expression of Trp53 is possible in spermatocytes of mice and in spermatogonia and spermatocytes of rats and humans.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…This finding may be one of the reasons for diminished sperm count after exposure of spermatogonia. The increased apoptosis is most likely associated with increased levels of Trp53 protein [43]. As Yin et al [46] note, predominant expression of Trp53 is possible in spermatocytes of mice and in spermatogonia and spermatocytes of rats and humans.…”
Section: Discussionmentioning
confidence: 98%
“…The damage caused by radiation may result in cell death or modifications that can affect the normal functioning of organs and tissues. The loss of male germ cells after exposure to ionising radiation is mainly attributed to apoptosis [43]. Sensitivity to radiationinduced apoptosis is characteristic for different types of cells present in testes [44,45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, the loss of male germ cells after exposure to ionizing radiation has been attributed to apoptosis. Liu et al demonstrated that absorbed doses of 25-200 mGy induced a significant increase in apoptosis in both spermatogonia and spermatocytes, with a maximal effect at 75 mGy (40).…”
Section: Small-scale Dosimetry Of Human Testes • Larsson Et Almentioning
confidence: 99%
“…These different types of germ cells differ remarkably in their susceptibility to radiationinduced effects according to their level of reproductive activity [5]. The effect on reproductive organs and behaviour by chronic exposure to radionuclides is one of major concerns.…”
Section: Introductionmentioning
confidence: 99%